2020
DOI: 10.1002/adsc.201901451
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3‐Keto Pyridines from the Conjugated Allenone – Alkynylamine Oxidative Cyclization Catalyzed by Supported Au Nanoparticles

Abstract: Recyclable supported Au nanoparticles on TiO2 catalyze the cyclization of N‐propargyl or N‐homopropargyl β‐enaminones followed by dehydrogenation (aromatization) leading to substituted 3‐keto pyridines or 4‐picolines in very good yields. This pathway is in contrast to their known cyclization in the presence of Au(I) or Au(III) catalysts which provides 1,4‐oxazepines, instead. The enaminones are formed in situ upon mixing a conjugated allenone or allenyl ester with the alkynylamine, thus the pyridine‐forming tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, an alternative pathway, with the chemisorbed species I being transformed, via a dehydrogenation process, into the intermediate III, and after protodeauration to the benzimidazole, could also take place. Relevant dehydrogenation pathways are also proposed in the AuNP-catalyzed transformation of 1,2-dihydroquinolines to the corresponding quinolones [91], as well as in the synthesis of pyridines from the in situ generated N-propargyl enaminones [92]. Herein, partial charges were used for the intermediates I and III, based on previous calculations on the bonding nature of chemisorbed intermediates on Au clusters [93,94].…”
Section: Recycling and Mechanistic Studiesmentioning
confidence: 99%
“…However, an alternative pathway, with the chemisorbed species I being transformed, via a dehydrogenation process, into the intermediate III, and after protodeauration to the benzimidazole, could also take place. Relevant dehydrogenation pathways are also proposed in the AuNP-catalyzed transformation of 1,2-dihydroquinolines to the corresponding quinolones [91], as well as in the synthesis of pyridines from the in situ generated N-propargyl enaminones [92]. Herein, partial charges were used for the intermediates I and III, based on previous calculations on the bonding nature of chemisorbed intermediates on Au clusters [93,94].…”
Section: Recycling and Mechanistic Studiesmentioning
confidence: 99%
“…Although in Scheme 3 we provide for clarity full charges in the intermediates, in fact, they should be partial, given that the Au n −carbon σ bonds are partially polarized. 22,29 Given this interesting result, we next examined the scope and limitations of this transformation in a series of skipped symmetrical and unsymmetrical aryl or alkyl diynones (Table 2). The general characteristic is that aryl or alkyl diynones cyclize equally well under the same reaction time scale affording solely γ-pyrones without any detectable amounts of the isomeric 3(2H)furanones.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A reasonable explanation is that the low coordinated Au(0) atoms on the corners or edges of the nanoparticles exhibit partial Lewis acidic behavior, and also it has been reported that the synergism between Au clusters and the support produces electron-deficient active sites on the Au particles . Thus, ω-alkynylfurans, aryl propargyl ethers, 1,6-enynes, N -1,6-enynes, 2-alkynylanilines, propargylic ureas, and γ-acetylenic carboxylic acids undergo intramolecular cyclization via alkyne activation on Au NPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[209] The transformation is also extended to homopropargyl amine 447, yielding related pyridines 445 b with good yields (Scheme 77a). [209] A different strategy to build the pyridine ring from allenones is based on a formal [4 + 2] cycloaddition between 1,2-allenyl ketones 2 and azadienes 448 (Scheme 77b). [210] In this case, a base-promoted stepwise reaction mechanism is proposed, starting with the deprotonation of allenones 2 with K 2 CO 3 to give carbanions 450.…”
Section: Synthesis Of Nitrogen Heterocyclesmentioning
confidence: 99%